The Cultural Identity of Finnish Muslim Converts: Challenges and Realities - Ahmad, Iman; Shehu, Fatmir (IIUM Journal of Religion and Civilisational Studies, 2026)
This study seeks to examine the cultural identity of Finnish Muslim converts, emphasising the challenges and realities faced by them. Its goal is to explore the challenges faced by the Finnish Muslim converts, not only because they need assistance in integrating into the Muslim ummah, but also because they are a pivotal bridge between native non-Muslims and the acceptance of Muslims with their Islamic identity as part of Finnish society. The Finnish Muslims are of diversity of ethnicities comprising mostly refugees, asylum-seekers, and their families, who have been throughout the wave of migration to Finland from the late 1980s and have been perceived negatively by the Finnish public. Furthermore, Islam is perceived as an immigrant religion, and as such “Otherisation” is the challenge experienced by Muslims, who are marginalised by the native Finnish community. Such treatment includes the native Finnish Muslims (converts), who have left their previous traditions and culture. This research is literature-based, to which descriptive, historical, and analytical methods are applied. The main challenges faced by Finnish-Muslim converts from the perspective of cultural identity are addressed in this study through a discussion on (1) the arrival of Tatars in Finland, (2) the second wave of Muslims, (3) perceptions of Islam and Muslims in Finland, (4) Lutheranism in Finland, (5) ethnicity within Finnish cultural identity, (6) challenges faced by Finnish Muslim converts, (7) realities, and (8) future outlook. It is concluded by this study that Finnish Muslim converts navigate a complex intersection of religion, culture, and national identity, often facing “Otherisation” and “marginalisation,” while striving to integrate Islamic teachings with Finnish values, emphasising the need for better religious understanding and stronger efforts to address Islamophobia, while maintaining their bridge to their Finnish identity. This could, in the future, also pave the way for interreligious dialogue.